English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

If you can just walk me through the steps for each problem, I'd really appreciate it... Thank you so much in advance !!

f(x) = x+1

g(x) = 2x^2 +5

h(x) = 3x-1

1. Find f(g(x))?

2. Find h(f(g(x))?

3. Find g(h(f(x))?

2007-01-18 18:44:17 · 3 answers · asked by Anonymous in Science & Mathematics Mathematics

3 answers

When you have stuff like f(g(x)) and h(f(g(x)) you put the inside equation in place of x.

1. f(g(x))=g(x)+1
you put in g(x) to get the answer: f(g(x))=(2x^2+5)+1
simplify that and f(g(x))=2x^2+6

2. h(f(g(x))=3(f(g(x))-1
put in f(g(x)): h(f(g(x))=3(2x^2+6)-1
Simplify: h(f(g(x))=6x^2+17

3. g(h(f(x))=2(h(f(x)))^2+5=
2(3(x+1)-1)^2+5=
2(3x+2)^2+5=18x^2+12x+13
g(h(f(x))=18x^2+12x+13

2007-01-18 18:50:36 · answer #1 · answered by Ben B 4 · 0 0

Given:

f(x) = x + 1
g(x) = 2x² + 5
h(x) = 3x - 1

Work the problems from the inside out.

1. f(g(x)) = f(2x² +5) = (2x² +5) + 1 = 2x² +6

2. h(f(g(x))) = h(f(2x² +5)) = h{(2x² + 5) + 1} = h(2x² + 6)
= 3(2x² + 6) - 1 = 6x² + 18 - 1 = 6x² + 17

3. g(h(f(x))) = g(h(x + 1)) = g{3(x + 1) - 1} = g(3x + 3 - 1)
= g(3x + 2) = 2(3x + 2)² + 5 = 2(9x² + 12x + 4) + 5
= 18x² + 24x + 8 + 5 = 18x² + 24x + 13

2007-01-19 03:25:47 · answer #2 · answered by Northstar 7 · 0 0

You should put the given function instead of x
f(g(x)) = 2x^2+5 +1 = 2x^2 +6

h(f(g(x)) = 3*(2x^2+6) - 1 =6x^2 +17

h(f(x))= 3(x+1)+1 = 3x+4
g(h(f(x)) = 2*(3x+4)^2 +5 =18x^2+48x+37

2007-01-19 08:07:10 · answer #3 · answered by santmann2002 7 · 0 0

fedest.com, questions and answers